Frontiers and new vistas in women in management research - Sekaran, Uma (Journal of business ethics, 1990)
This paper addresses the theoretical and methodological issues in women in management research, as the field emerges out of its adulthood and steps into the age of maturity. The four fundamental issues addressed are (i) the need to conduct extensive research in this area; (ii) the need for synthesizing previous research findings and establishing a solid theory base on which further work can progress; (iii) the appropriate methodologies for generating further knowledge in the area; and (iv) future directions for research on women in management, taking both a “basic” and “applied” research perspective.